Optimalisasi Manajemen Bisnis bagi Pelaku UMKM - Izzaty, Khairina Nur; Pujiastuti, Yanti; Wahyuni, Asri Nur; Yuliana, Rahmi; Rinwantin, Rinwantin; H, Suryakusuma Kholid (Fokus ABDIMAS, 2024)
In order to optimize sales and marketing of MSMEs to increase product sales as well as entrepreneurship training to revive the community economy in Tlogosari Kulon Village, Semarang. On this occasion, the STIE Bank Bpd Jateng Community Service ABDIMAS TEAM aimed at providing knowledge and skills to help MSMEs improve their business management. This activity includes outreach and counseling to MSME players regarding the basics of entrepreneurship, marketing and financial recording. assisting this business by providing insight and understanding for sellers to implement online sales and how to promote via digital online. This activity also helps to re-brand logos and product packaging, creating new product variants. Meanwhile, for the community, Community Service students want to help revive the economy during the current Covid-19 pandemic, namely by providing entrepreneurship training to make products that have marketable value. This activity really needs advice and moral and material support from all levels of society, and related agencies in realizing this activity in accordance with the approved funds